BLOOD GLUCOSE LEVELS ARE STRONGLY ASSOCIATED WITH VCAM-1 LEVELS IN PATIENTS WITH METABOLIC SYNDROME - Achmad, Nurjannah; Andintama, Salma; Inayati Rakhmat, Iis (Fakultas Kedokteran Gigi Unjani, 2025)
Metabolic syndrome is a combination of metabolic risk factors that cause cardiovascular disease. These risk factors include high blood pressure, obesity, low HDL levels, hyperglycemia, and hypertriglyceridemia. This study aims to investigate the relationship between the components of metabolic syndrome and VCAM-1 levels, a marker of endothelial dysfunction, in patients with metabolic syndrome residing in RW 01 Cibeber, Cimahi. The study was conducted using a cross-sectional design with analytical descriptive methods. The respondents were 44 people who were taken by consecutive sampling. The components of the metabolic syndrome based on the NCEP ATP-III criteria include waist circumference, blood pressure, triglyceride levels as measured by the colorimetric GPO-PAP (Glycerol Peroxidase Phosphate Acid) enzymatic test, fasting blood glucose levels using the GOD-PAP (Glucose Aminoantypirin Oxidase-Peroxidase), and HDL cholesterol levels with the Trinder PEG (Polyethylene Glycol) precipitation method. VCAM-1 levels were examined using a quantitative enzyme-linked immunosorbent assay method as a marker of endothelial dysfunction. The results showed that most subjects had three or more of the five components (50%), and more than half of the subjects had high levels of VCAM-1 (63.6%). In addition, there was a significant relationship between the two components of the metabolic syndrome and VCAM-1 levels, namely fasting blood sugar (p = 0.000; r = 0.570) and triglycerides (p = 0.001; r = 0.501). Increased blood sugar causes changes in insulin signaling, interfering with NO production and increasing pro-inflammation, which in turn increases VCAM-1. At high triglyceride levels, it causes oxidative stress, leading to damage to vascular tissue, which in turn increases VCAM-1 DOI : 10.54052/jhds/v5n2.p199-212